Female collectors in the early 20th century: collecting and displaying the Greek nation - Bounia, Alexandra (Hamburger Journal für Kulturanthropologie (HJK), 2015)
This paper aims to discuss the role of female collectors in Greece in the early 20th century. It focuses on two case studies, Loukia Zygomala, the founder of a small museum in Attica, and Eleni Stathatos, a passionate collector who donated her collection to three Athenian institutions. It is argued that their collections and their contribution to Greek institutions can be understood as part of an effort made by women of the upper classes to participate in the construction of Hellenic national identity. Furthermore, this article aims to shed light on perceptions and practices of object presentation and exhibition design in Greece during the same period.